(untitled) (Academia Journal of Medicine, 2019)
Background: Megaloblastic Anaemia and pancytopenia are common medical problems, Vitamin B12and folic acid deficiencies are common causes for megaloblastic Anaemia. Pancytopenia is a condition where bone marrow becomes hypo plastic fails to produce mature blood cells, causes include myelodysplasia leukemia’s, drugs and ionizing radiation and always associated with decreased reticulocyte count. Megaloblastic Anaemia is commonly due to dietary deficiency and pregnancy. Aim: To study about megaloblastic Anaemia& pancytopenia. Subjects and Methods: In our study we have examined 120 Anaemia patients for 1 year.out of these 120 patients most of than are having Iron deficiency Anaemia 32 patients are having megaloblastic Anaemia and 26 patients are having pancytopenia. after complete history taking and clinical exmination we have send the blood samples for investigations. Results: Total no. of megaloblastic Anaemia were 32 patients Males 18, Females 14 and the total no. of pancytopenia patients were 26 out of these 26, 15 were Males and 11 were Females common age group is 20 years and 40 years, The clinical features are fatigue, shortness of breath, parenthesis’s, Fever, Splenomegaly pallar are present in most of the cases. Conclusion: megaloblastic Anaemia and pancytopenia are common medical problems in India, especially rural areas, they should be suspected is pregnant woman with prolonged fever, Anaemia& bleeding tendencies and lympledinopathy.